Manajemen Hubungan Masyarakat dalam Mengembangkan Sarana dan Prasarana di Lembaga Pendidikan - Siti Nur Patimah; Moh. Ibnu Faruk Fauzi (Lembaga Pengembangan Kinerja Dosen, 2023)
Public relations management is a function of management that links educational institutions and the community. In developing facilities and infrastructure in educational institutions, it will impact public attention and concern regarding the quality of education. The research method used is a qualitative descriptive method. The research results show that 1) Public relations planning involves all parties related to the activity program being implemented, 2) Organizing the division of work, facilities and infrastructure coordinator, public relations coordinator in providing the facilities and infrastructure needed by students; 3) Implementing the public relations activity program, the school collaborates with the community by procuring facilities and infrastructure; 4) Public relations evaluation is carried out by comparing the program that has been established with the implementation of the program. Public relations evaluation is carried out by the school principal and deputy head of public relations.